The nomadic word in a research on teacher training in Visual Arts (Revista Apotheke, 2022)
This text presents the partial results of a research, still in progress, with the Degree in Visual Arts at the Santa Catarina State University, Brazil. During the data collection, we chose to observe and describe the words found in final papers of the year 2018, and they belong to students of that university degree, in two aspects: keywords and titles. In this research, the word works in a language system that is not just a representation, in the sense of a mirror, or as a concrete expression of the teaching formation of students, but rather as an open interstice in which teaching can arise. With this proposition, cartographies arise in which the word, as something nomadic, mobile, and wandering, proposes to indicate the clues of the papers developed in art and education by the undergraduates.
Keywords: Degree in Visual Arts; Art and Education; Nomadic; Wandering; Teacher Training